Analysis and Design of Morotai Tourism Village Information System (SIDEWITA) Based on Local Wisdom of Tokuwela and Babari Tradition - Sutresno, Stephen Aprius; Singgalen, Yerik Afrianto (Journal of Information Systems and Informatics, 2023)
This study focuses on optimizing the management system of tourism villages in Indonesia through the development of a contextual and relevant information system that caters to users' needs. Specifically, the study targets the Morotai Island Regency, where the tourism village management requires a website-based system capable of providing comprehensive information on attractions, accessibility, accommodation, and ancillary services to a broader market. The study uses the Software Development Life Cycle (SDLC) with a Waterfall approach to design the system, with a focus on the actors involved in the system, including tourists and prospective tourists (users as tourists), administrators and community members (users as a community), and stakeholders such as entrepreneurs and formal organizations supporting tourism (users as stakeholders). The resulting system, SIDEWITA, is expected to optimize the management of tourist villages in Morotai Island Regency. However, the study is limited to the design phase using the Waterfall approach.
Keywords: information system; tourism village; tourism; waterfall; SDLC; Morotai